The Role Of Financial Technology (Fintech) in MSMEs - Rheva Tiansyah Putri; Puji Isyanto; Neni Sumarni (Yayasan Riset dan Pengembangan Intelektual, 2023)
People can choose from various service items due to advances in information and technology. Internet services that have recently benefited the community, especially MSMEs, are financial technology (Fintech). Both the financial and economic sectors use this technology. Many fintech technologies help people in business and financial matters. Systems and services for fintech are becoming increasingly fast and simple. The purpose of researching this is to evaluate and understand the function of financial technology (Fintech) on the growth of Micro, Small and Medium Enterprises or MSMEs in the Subang area. Inevitably, capital, financing, and funding issues are significant problems in their business activities. Transactions with Fintech can greatly help BRI Link's MSMEs to grow their business and provide peace of mind against financial crises. The capital loan system through banks is rather tricky, especially for MSMEs that usually do not have complete financial reporting business processes. Therefore, it is interesting to see the role of the emergence of Fintech and its success for MSMEs. This research uses a descriptive qualitative approach. The results of this study indicate that MSMEs and the community can utilize Fintech because it is felt to have benefits to facilitate the operations of MSMEs, especially BRI LINK agents in Subang Regency. Fintech makes it easy for people to get online loan capital and for MSMEs to report their finances.